Hypertension testing and treatment in Uganda and Kenya through the SEARCH study: An implementation fidelity and outcome evaluation. - David J Heller; Laura B Balzer; Dhruv Kazi; Edwin D Charlebois; Dalsone Kwarisiima; Florence Mwangwa; Vivek Jain; Prashant Kotwani; Gabriel Chamie; Craig R Cohen; Tamara D Clark; James Ayieko; et al. (PLoS ONE)
Background Hypertension (HTN) is the single leading risk factor for human mortality worldwide, and more prevalent in sub-Saharan Africa than any other region [1]-although resources for HTN screening, treatment, and control are few. Most regional pilot studies to leverage HIV programs for HTN control have achieved blood pressure control in half of participants or fewer [2,3,4]. But this control gap may be due to inconsistent delivery of services, rather than ineffective underlying interventions. Methods We sought to evaluate the consistency of HTN program delivery within the SEARCH study (NCT01864603) among 95,000 adults in 32 rural communities in Uganda and Kenya from 2013-2016. To achieve this objective, we designed and performed a fidelity evaluation of the step-by-step process (cascade) of HTN care within SEARCH, calculating rates of HTN screening, linkage to care, and follow-up care. We evaluated SEARCH's assessment of each participant's HTN status against measured blood pressure and HTN history. Findings SEARCH completed blood pressure screens on 91% of participants. SEARCH HTN screening was 91% sensitive and over 99% specific for HTN relative to measured blood pressure and patient history. 92% of participants screened HTN+ received clinic appointments, and 42% of persons with HTN linked to subsequent care. At follow-up, 82% of SEARCH clinic participants received blood pressure checks; 75% received medication appropriate for their blood pressure; 66% remained in care; and 46% had normal blood pressure at their most recent visit. Conclusion The SEARCH study's consistency in delivering screening and treatment services for HTN was generally high, but SEARCH could improve effectiveness in linking patients to care and achieving HTN control. Its model for implementing population-scale HTN testing and care through an existing HIV test-and-treat program-and protocol for evaluating the intervention's stepwise fidelity and care outcomes-may be adapted, strengthened, and scaled up for use across multiple resource-limited settings.